Ensino de discriminações condicionais em bebês: avaliação do responder por exclusão e treino de emparelhamento de identidade com diferentes estímulos - Garcia, Lucas Tadeu (2010)
Studies on learning by exclusion and stimuli equivalence are usually conducted by means of conditional discriminations teaching procedures. Some recent studies have investigated important variables in procedures for teaching conditional discriminations to babies, both for the maintenance of the subjects in the task and for the establishment of conditional responding in babies. Considering the recent advances in the literature and seeking to develop procedures for investigating relational repertoires in infants, two studies were performed. The first study was divided into two parts whose objectives was: 1A) replicating and adapting to the child care center context a study about conditional discrimination teaching by exclusion for a baby of 17 months, in which photographs were used as stimuli and; 1B ) to evaluate the generality of the procedure employed in the previous study. The second study aimed to investigate the effect of using abstract stimuli and toys stimuli on an identity matching teaching procedure. In Study 1A, the three participants were trained a baseline auditory-visual conditional discriminations with familiar photographs. After that subjects were presented to exclusion and learning evaluation trials. The three participants (between 17 and 19 months) learned the baseline conditional discriminations and chose correctly in all exclusion trials, although they have not demonstrated learning by exclusion. In Study 1B the same procedure was used and only two of three children, aged between 15 and 18 months, learned the baseline relations, although all of them chose the correct stimulus in the exclusion trials. There was evidence of learning by exclusion for some children, however, the performance of infants in the novelty control trials suggested that children could be choosing based on such bias. The results suggest that the presented procedure is a useful tool for the study of exclusion responding in babies and thus enables further investigations on the process. In Study 2, two babies of 17 and 20 months were submitted to an identity matching training with abstract shapes or toys used as discriminative stimuli. The stimuli presentation was made by a mechanical apparatus that allowed the exposure of stimuli in closed and open windows. The programmed consequences varied according to the stimuli training condition. Babies have not learned the identity conditional discriminations in any stimuli conditions, although there was a greater number of corrects choices when the stimuli used were abstract shapes. Nevertheless, it was not possible to obtain conclusive evidence about the effectiveness of the use of those different stimuli conditions on the infant s conditional discrimination learning.